Municipal elections and national crisis: electoral disputes in Brazil in 2016 - Cervi, Emerson Urizzi (2019)
The 2016 marked the impeachment of President Dilma Rousseff (PT) and one of the hardest political crises since the Brazilian redemocratization in the early 1980s. One of the parties most affected by the national crisis was the “Partido dos Trabalhadores”. It remains to be seen how much the negative visibility of the party in the national arena has impacted local disputes. The article intends to analyze the results of the 2016 elections from aggregated variables. The democratization index is used to identify patterns of local democracy and to associate the performance of the major parties with these standards. The objective is to verify which parties have achieved better results in the current political conjuncture. The performance of candidates for councillor and mayor in the 5,600 municipalities in 2016 elections is analyzed.